The impact of behavioral and environmental factors on cancer mortality in G7 countries: a 20-year ecologic study - Caglar, Yezdan; Ozdal, Macide Artac (Frontiers in Public Health, 2025)
BackgroundThe Cancer death rates prevails as a critical challenge on health systems globally. Whilst various factors such as economics and lifestyle factors are predicted to be influential, it is important to explain these relationship scientifically to develop targeted public health interventions.ObjectivesThe investigation within this study concerns the interconnections between the rates of death arising from Cancer and pivotal lifestyle and economic factors of the populations within the economically advanced countries of the G7 (Germany, the United Kingdom (UK), The United States of America (USA), Canada, France, Italy, and Japan) over 20 years, from the year 2000 until 2020.MethodsThe data used in this study, including GDP (in United States Dollars USD - $) influence, obesity rate, pollution levels, population size, the prevalence of smoking, and the cancer death rates were collected from World Bank and Organization for Economic Co-operation and Development (OECD). Descriptive statistics, multiple linear regression, ANOVA, the case Processing Summary, and Principal Component Analysis were carried out to determine the distribution of data and interrelationships between independent and dependent variables.ResultsThe findings of the study disclosed that the variables explained 58% of the variance in cancer mortality (R2 = 0.580). Definite connections between smoking prevalence, years of life lost, levels of obesity, the level of pollution, and the cancer death rate were established.ConclusionThe study emphasizes the importance of targeting modifiable risk factors such as smoking, pollution, and obesity in cancer prevention and management. It highlights the importance of public health strategies focused on reducing these risk factors through targeted interventions. Additionally, equitable healthcare distribution must be considered in shaping effective policies to reduce cancer mortality.